Huang's three-step maneuver shortens the learning curve of laparoscopic spleen-preserving splenic hilar lymphadenectomy. (December 2017) - Huang, Chang-Ming; Huang, Ze-Ning; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei; Wang, Jia-bin; Lin, Jian-Xian; Jun, Lu; Chen, Qi-Yue; Cao, Long-long; Lin, Mi; Tu, Ru-Hong
Abstract: Background: The goal of this study was to investigate the difference between the learning curves of different maneuvers in laparoscopic spleen-preserving splenic hilar lymphadenectomy for advanced upper gastric cancer. Methods: From January 2010 to April 2014, 53 consecutive patients who underwent laparoscopic spleen-preserving splenic hilar lymphadenectomy via the traditional-step maneuver (group A) and 53 consecutive patients via Huang's three-step maneuver (group B) were retrospectively analyzed. Results: No significant difference in patient characteristics were found between the two groups. The learning curves of groups A and B were divided into phase 1 (1–43 cases and 1–30 cases, respectively) and phase 2 (44–53 cases and 31–53 cases, respectively). Compared with group A, the dissection time, bleeding loss and vascular injury were significantly decreased in group B. No significant differences in short-term outcomes were found between the two maneuvers. The multivariate analysis indicated that the body mass index, short gastric vessels, splenic artery type and maneuver were significantly associated with the dissection time in group B. No significant difference in the survival curve was found between the maneuvers. Conclusions: The learning curve of Huang's three-step maneuver was shorter than that of the traditional-step maneuver, and the former represents an ideal maneuver for laparoscopic spleen-preserving splenic hilar lymphadenectomy.To shorten the learning curve at the beginning of laparoscopic spleen-preserving splenic hilar lymphadenectomy, beginners should beneficially use Huang's three-step maneuver and select patients with advanced upper gastric cancer with a body mass index of less than 25 kg/m 2 and the concentrated type of splenic artery. Highlights: There were several operative approaches for laparoscopic spleen-preserving splenic hilar lymphadenectomy (LSPL). For mastering the skill, surgeon needs through learning curve. But there were still not the study of the learning curve of different maneuver for LSPL. So, we used the cumulative sum method (CUSUM) to systematically compare the learning curves. We compare the learning curves and think the Huang's three-step maneuver was an ideal maneuver for LSPL.